Recovery of short-chain organic acids (SCOAs) obtained from anaerobic fermentation process - Ghalibaf, Maryam; Pap, Nora; Vainio, Markku; Honkala, Niina; Rasi, Saija (Elsevier, 2024)
hort-chain organic acids (SCOAs) are the intermediates in the anaerobic fermentation process, and can be used in food, textile, and pharmaceutical industries to produce different end use products. SCOAs can be separated, purified, and concentrated by different processes, such as distillation, extraction or membrane-based systems. SCOAs production adds more profitable possibilities to an acidic fermentation process by integration these marketable acids as highly concentrated mixtures with other refinery processes. The present study investigated two approaches for recovering of SCOAs: i) the production of clarified SCOAs liquid by microfiltration (MF) and then performing their concentration by reverse osmosis (RO) and ii) the recovery and concentration by the so-called integrated neutralization and acidified reaction method. The results of MF showed that some SCOAs were retained in the retentate together with the solids. However, in the following RO treatment, SCOAs could be successfully concentrated with a yield retention of over 90 % from the SCOAs liquid. In the latter method, a color-free SCOAs liquid was obtained with an increase in the total SCOAs concentration from 23 g/L to 146 g/L.
Keywords: concentration; short-chain organic acids (SCOAs); membrane technologies; recovery; purification; anaerobic fermentation